A New Composite Electrode Applied for Studying the Electrochemistry of Insoluble Particles: α‐HgS. Issue 40 (19th June 2018) - Yang, Minjun; Compton, Richard G.
Abstract: The redox chemistry of solid α‐HgS particles is revealed using a carbon/PVDF composite containing α‐HgS, carbon black, polyvinylidene fluoride (PVDF). The electrochemical behaviour of the carbon/PVDF composite is first characterised with three water insoluble organic solids. Then the reduction of solid α‐HgS particles is investigated and found to occur at a high negative potential, −1.82 V versus saturated mercury sulphate reference electrode, to form metallic mercury and sulphide ions. The subsequent oxidation of metallic mercury and sulphide occurs at +0.24 and −0.49 V versus MSE respectively. Abstract : A new carbon composite was used to immobilise solid particles and facilitate the electrochemical analysis of α‐HgS. The electrochemical behaviour of this new carbon composite was first validated before revealing the redox chemistry of α‐HgS. The reduction of α‐HgS and the subsequent oxidation of metallic mercury and sulphide anion were seen in a single cyclic voltammetric experiment.